If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2xyz + yz = 0 Solving 2xyz + yz = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1yz' to each side of the equation. 2xyz + yz + -1yz = 0 + -1yz Combine like terms: yz + -1yz = 0 2xyz + 0 = 0 + -1yz 2xyz = 0 + -1yz Remove the zero: 2xyz = -1yz Divide each side by '2yz'. x = -0.5 Simplifying x = -0.5
| 3.2x^2-16.8x-16.8=0 | | 54.2+x=-45.8 | | 9y^2-81y+1=0 | | x+34.2=67.1 | | 6x+7-2x+4=4(3x-5)-17 | | 9=0.4x-8 | | -81=-92.6+x | | M=2(30)+80 | | 2a^2+2=-7 | | M=2x+80 | | 28y+16z= | | -x+58.1=89 | | x+(-67.1)=54.6 | | 65=-16t^2+vt+s | | x^2-4x-12.8=0 | | 4(3x-1)+10= | | 2lnx=ln(6+x) | | -67.5+x=22.7 | | 6y+18y= | | x+38.6=-82.1 | | 7x+10y=12 | | (a^2b^4)(ab^5)= | | 85x+55x=420 | | 75.5=x+95.2 | | (V-6)(v-2)=0 | | 4C^2-35C+49=0 | | -x+12.8=33.2 | | 9(t-6)+5t=7(2t+5)-8 | | (x-3)(x+7)=o | | 4x(3x+6)=2(x-7) | | 5n^2+7=132 | | 0.1(8)+x=0.4(8+x) |